Proceedings of the 2013 IEEE/ACM International Conference on Advances in Social Networks Analysis and Mining 2013
DOI: 10.1145/2492517.2492621
|View full text |Cite
|
Sign up to set email alerts
|

The social media genome

Abstract: Abstract-Information propagation in social media depends not only on the static follower structure but also on the topicspecific user behavior. Hence novel models incorporating dynamic user behavior are needed. To this end, we propose a model for individual social media users, termed a genotype. The genotype is a per-topic summary of a user's interest, activity and susceptibility to adopt new information. We demonstrate that user genotypes remain invariant within a topic by adopting them for classification of … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
5
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 31 publications
(6 citation statements)
references
References 17 publications
0
5
0
1
Order By: Relevance
“…Furthermore, they showed that, while some users create connections mostly based on friendship, others are more guided by the content that users produce and share. Bogdanov et al provide a model of pre-specified topics and verified the consistency of their use by Twitter users, they also applied this to predict influencers and to minimize the latency in information dissemination [4]. Meyers et al [9] were interested in how the rise of abrupt changes in the information flow dynamics influences the creation and removal of links.…”
Section: Related Workmentioning
confidence: 99%
See 2 more Smart Citations
“…Furthermore, they showed that, while some users create connections mostly based on friendship, others are more guided by the content that users produce and share. Bogdanov et al provide a model of pre-specified topics and verified the consistency of their use by Twitter users, they also applied this to predict influencers and to minimize the latency in information dissemination [4]. Meyers et al [9] were interested in how the rise of abrupt changes in the information flow dynamics influences the creation and removal of links.…”
Section: Related Workmentioning
confidence: 99%
“…We infer topics from clusters of highly associated hashtags in messages exchanged by users. This allows us to capture topics exposing latent higher-level semantic entities without the need of an external ontology or manual classification step [2,3,4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…A20 Classifying ecommerce information sharing behaviour by youths on social networking sites 2011 [38] A21 Clustering memes in social media 2013 [39] A22 Collaborative filtering based on collaborative tagging for enhancing the quality of recommendation 2010 [40] A23 Collaborative visual modeling for automatic image annotation via sparse model coding 2012 [41] A24 Confucius and its intelligent disciples: integrating social with search 2010 [42] A25 Content Feature Enrichment for Analyzing Trust Relationships in Web Forums 2013 [43] A26 Content Matters : A study of hate groups detection based on social networks analysis and web mining 2013 [44] A27 Co-training over Domain-independent and Domain-dependent features for sentiment analysis of an online cancer support community 2013 [45] A28 Data-Mining Twitter and the Autism Spectrum Disorder : A Pilot Study 2014 [46] A29 Decision Fusion for Multimodal Biometrics Using Social Network Analysis 2014 [47] A30 Detecting Deception in Online Social Networks 2014 [48] A31 Enhancing financial performance with social media: An impression management perspective 2013 [49] A32 Enriching short text representation in microblog for clustering 2012 [50] A33 Estimating the helpfulness and economic impact of product reviews: Mining text and reviewer characteristics 2011 [51] A34 A56 The potential of social media in delivering transport policy goals 2014 [74] A57 The social media genome: modeling individual topic-specific behavior in social media 2013 [75] A58 Topic-sensitive influencer mining in interest-based social media networks via hypergraph learning 2014 [76] A59 Twitter, MySpace, Digg: Unsupervised Sentiment Analysis in Social Media 2012 [77] A60 Unsupervised and supervised learning to evaluate event relatedness based on content mining from socialmedia streams 2012 [78] A61 Using explicit linguistic expressions of preference in social media to predict voting behavior 2013 [79] A62 Using inter-comment similarity for comment spam detection in Chinese blogs 2011 [80] A63 Using Sentiment to Detect Bots on Twitter: Are Humans more Opinionated than Bots? 2014 [81] A64 Using social media to enhance emergency situation awareness 2012 [82] A65 Web data extraction, applications and techniques: A survey 2014 [83] A66 What's in twitter: I know what part...…”
Section: A40mentioning
confidence: 99%
“…Some other greedy-based algorithm to get top-K influential users in social networks are proposed by [Du et al 2013;Wang et al 2010], and an algorithm is proposed by [Gomez-Rodriguez et al 2012] to infer website influence in blogs. In addition, topic-specific influence and backbone structures in networks are studied by [Bi et al 2014;Bogdanov et al 2013].…”
Section: Related Workmentioning
confidence: 99%